Regulation and cell-type-specific activity of a promoter located upstream of the latency-associated transcript of herpes simplex virus type 1. - Batchelor, A H (1990)
To identify promoter regions which control expression of the latency-associated transcript (LAT) of herpes simplex virus type 1 (HSV-1), we constructed a series of recombinant vectors in which various sequences upstream of LAT were linked to the chloramphenicol acetyltransferase gene and tested for expression efficiency by transfection into tissue culture cells. In HeLa cells no activity was observed from the region (-250 to +201) immediately surrounding the nominal 5' end of LAT, but high levels of activity were observed by using different fragments within the region -1267 to -594. This promoter activity was largely contained within the 140-base-pair region from -797 to -658 and was 20- to 50-fold stronger than typical HSV delayed-early promoters and at least as strong as the activity from the simian virus 40 (SV40) enhancer-promoter region or the HSV immediate-early 110,000-Mr (IE110K) promoter region. In human neuroblastoma cells (IMR-32), there was a dramatic switch in relative activities in favor of the LAT promoter, so that it was 45- and 200-fold stronger than the IE110K and SV40 constructs, respectively. Furthermore, optimal activity in the neuroblastoma cells required sequences within the region -1267 to -797. This region had little effect on activity in HeLa cells. We also show that the LAT promoter activity was very efficiently repressed by the IE175K protein. From internal deletion analysis, the site of repression was located within a 55-base-pair region just downstream of a potential TATA box. This region exhibited a high degree of homology with the IE175K cap site and may be a binding site for the IE175K protein.